ALTERNATIF TEKNOLOGI PENGOLAHAN AIR UNTUK MEMENUHI KEBUTUHAN AIR BERSIH DI DAERAH PEMUKIMAN NELAYAN Studi Kasus Perencanaan Penyediaan Air Bersih di Daerah Pedesaaan Nelayan Kab. Pasir, Kalimantan Timur - Hernaningsih, Taty; Yudo, Satmoko (Center for Environmental Technology, 2007)
Primary water source of people in Ã‚Â fisherman area in Kabupaten Pasir, Kalimantan Timur for daily water need generally is from Ã‚Â surface waterÃ‚Â or deep well. Surface water is affected by water tide of sea water, so that almost all the timeÃ‚Â in a year the water quality is salty or brakish. Beside high salt concentration, deep well quality Ã‚Â is also worst.Ã‚Â This is caused by poor environmental sanitation of fisherman community.Ã‚Â Rainy water use as water source alternative in problem solving for limited water drinking only provide in rainy season. Other alternative, people must find from other area where is far from their house or buy water with expensive price. To solve this critical problem is required the application of suitableÃ‚Â water treatment technology.Ã‚Â This water treatment Ã‚Â technology must produce drinking water that meet technical standard andÃ£â‚¬â‚¬ the technology is applicable, easy and cheap in operation and maintenance because it is hoped that community in that area can manage, operateÃ‚Â and maintenance.Ã‚Â Kata Kunci : Penduduk nelayan, penyediaan air bersih, teknologi pengolahan air bersih.